Розробка екологічно чистої дослідно-промислової технології виробництва нанодисперсних оксидів - Tarasevich, U. S.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
Developing scientific basis of chloride technology for nanodisperse oxides production is necessary for creation of ecologically safety technology for obtaining ultrapure metals, silicon, and their oxides, hetero-organic and other compounds. The idea of proposed technology consists in usage of ecologically harmful chlorine-containing products by their regeneration and returning to the technology process with obtaining chlorine by closed cycle. The synthesis of pyrogenic titanium and silicon oxides is based on the preparation of fugitive chlorine-containing compounds of these elements followed by oxidation or hydrolysis, mostly in the flame of air-hydrogen burner. New method of pyrogenic oxide synthesis contains merged in a joint technological cycle processes of preparation of initial chloride compounds in the flame of air-hydrogen burner, treatment of oxide surfaces, and isolation of the products. In order to intensify chemical interaction of components, some part of components is returned from the exit to the entrance of the reactor. Movement of components in the reactor is created by its rotation relatively to an axis located to bevel way to the horizon. The control of oxide synthesis with usage of adjustable level-by-level burning of the initial mixture in a flame allows us to create ecologically pure closed cycle and to increase productivity of the method, to improve the quality of production, to expand the types of raw materials and to decrease power consumption of the production.